No evidence of differences in cognitive control in children with autism spectrum disorder or obsessive-compulsive disorder: an fMRI study - Gooskens, Bram; Wolf, Isabella; Brandeis, Daniel (Developmental cognitive neuroscience, 2018)
Repetitive behaviors are among the core symptoms of both Autism Spectrum Disorder (ASD) and Obsessive-Compulsive Disorder (OCD) and are thought to be associated with impairments in cognitive control. However, it is still unknown how deficits in cognitive control and associated neural circuitry relate to the quality or severity of repetitive behavior in children with these disorders. Therefore, we investigated the behavioral and neural correlates of cognitive control using a modified stop-signal task in a multicenter study of children (aged 8-12 years) with ASD, OCD and typically developing (TD) children (N = 95). As both ASD and OCD have high levels of comorbidity with Attention Deficit/Hyperactivity Disorder (ADHD), we did an exploratory analysis addressing ADHD-symptoms. We found that children with ASD and OCD did not show deficits in cognitive control or changes in brain activity in task-relevant neural networks when compared to TD children. However, increased activity in prefrontal brain areas was associated with increased symptoms of comorbid ADHD. As such, this study does not support differences in cognitive control or associated neural circuitry in children with ASD and OCD, but rather suggests that changes in cognitive control in these disorders may be related to symptoms of comorbid ADHD.
Published online ahead of print
Gesehen am 13.05.2019